Edukasi Pajak Kaum Millenial Berbasis Web Games - Agustine Dwianika; Augury El Rayeb; Fitriyah Nurhidayah (Jurnal Pengabdian Pada Masyarakat, 2022)
WEB GAMES-BASED MİLLENNİAL TAX EDUCATİON. This Community Service Activity (PkM) aims to provide solutions for the Subject Teachers' Conference (MGMP) on: 1). declining interest in learning for high school students during the pandemic; 2). lack of attractive tax teaching support facilities and infrastructure at the high school level; 3). lack of knowledge and skills of teachers in technology-based learning, especially taxation subjects. In addition, to support partner programs as well as the government's national program in creating a tax-aware golden generation in 2045, the PkM team utilizes research on tax assistance activities, tax education, and the use of tax technology that has been done previously by: (1) formulating two types of easy games and already known by students, namely Snakes & Ladders and Tax Uno Cards, have become web-based games to make them more attractive; (2) direct introduction of the two web games to accounting teachers and develop input from teachers, in order to improve the program including facilities and infrastructure; (3) direct socialization to students in a series of Web games for the Tax Awareness Gold Generation which were made interactive, competitive and interesting. The results show an increase in the learning interest of 100 students involved, obtaining support for facilities and infrastructure, and increasing teacher knowledge and skills in technology-based learning in taxation subjects by more than 70%. Participants feel that web games-based tax learning is more fun as enrichment material and test preparation activities are more fun and more competitive than the usual practice questions.